Forest law enforcement and rural livelihoods - Kaimowitz, D. (2003)
International concern about illegal forestry activities has grown markedly. Asian, African, and European governments have held high-level regional conferences on Forest Law Enforcement and Governance (FLEG). Indonesia has signed path-breaking Memoranda of Understanding on illegal logging with the United Kingdom, China, and Norway. The Convention on Biological Diversity, the United Nations Forum on Forests, the International Tropical Timber Organisation, and the G8 have all issued forceful statements, and incorporated the issue in their work plans. The European Commission has committed itself to formulating a European FLEG Action Plan. Japan and Indonesia have initiated an Asian Forest Partnership, with a major focus on illegal logging. Global Witness, the Environmental Investigation Agency, Transparency International, Greenpeace, Global Forest Watch, and Friends of the Earth have raised public awareness about the problem.